The Effect of Product Quality, Trust, and E-Wom on Purchasing Decisions for The Originote products on Tiktokshop - Ruma Isyah Putri Mahing; Nora Pitri Nainggolan (LPPM Universitas Buddhi Dharma, 2024)
In a time marked by technological advances and increasing consumer knowledge, the skin care industry is also experiencing significant changes. This research focuses specifically on customers of The Originote products in Batam City who have interacted with the brand through the TikTok Shop. This study focuses on a specific age group, namely 16-30 years and examines four important factors: product quality, trust, e-WOM (Electronic Word of Mouth), and purchasing decisions. Analysis was carried out on 100 participants who met certain research criteria, using a quantitative research approach. Questionnaires were used to collect data, which was then analyzed using SPSS version 25. The research began by conducting validity and reliability tests to verify the quality of the data. Next, a classical assumption test was carried out which included normality, multicollinearity and heteroscedasticity tests to improve the quality of the data before hypothesis testing. Hypothesis analysis uses multiple linear regression, coefficient of determination test, as well as the t test and F test. The conclusion of this research is that the purchasing decision variable (X1) has a positive influence on the decision to purchase The Originote products at the TikTok Shop. Trust as a variable has a positive influence on purchasing decisions for The Originote products at the TikTok Shop (X2). The electronic word-of-mouth (e-WOM) factor has a beneficial impact on purchasing choices made for The Originote products on the TikTok Shop. The variables product quality (X1), trust (X2), and e-WOM (X3) have quite a large influence on purchasing decisions when considered together.